Hemofilia adquirida asociada a la infección por SARS-CoV2 - Catarina Medeiros; Daniela Brito; Rita Serras Jorge (Sociedade Galega de Medicina Interna, 2022)
SARS-CoV2 infection has been found to be associated with coagulopathy. Although thrombotic complications have been more frequently reported, hematologic autoimmune disorders have also been described. We present the case of a 73-year-old man, with a history of SARS-CoV2 infection (January 2021), who came to the emergency department three months post infection, with complaints of left hip and knee pain, that turned out to be a substantial thigh hematoma. Analysis showed a normocytic/ normochromic anaemia (9,0 g/dL), prolonged aPTT (63.2 seconds; normal range 24.7-39.0 sec.), with normal prothrombin time. We arrived at a diagnosis of Acquired Haemophilia A. Treatment was promptly started, with clinical and laboratory improvement. After the vaccination to SARS-CoV2, a relapse was observed. Acquired Haemophilia A is a rare, autoimmune disease, distinguished by the presence of inhibitors against factor VIII. It's characterised by subcutaneous hematomas and muscle bleeding, with prolonged aPTT. SARS-CoV2 infection has already been mentioned as a possible cause.